Ucale

# Integration of some special irrational algebraic functions

In this section,Â  we shall discuss four integrals of the formÂ $\displaystyle \int { \frac { \phi \left( x \right) }{ P\sqrt { Q } } } dx$ when P and Q are polynomial functions of x.

### Type I

Integrals of the formÂ $\displaystyle \int { \frac { \phi \left( x \right) }{ P\sqrt { Q } } } dx$ where P and Q both are linear function of x

To evaluate this type of integrals we putÂ $\displaystyle Q={ t }^{ 2 }$ i.e., to evaluate integrals of the formÂ Â $\displaystyle \int { \frac { 1 }{ \left( ax+b \right) \sqrt { cx+d } } } dx\quad put\quad cx+d={ t }^{ 2 }$

The following examples illustrate the procedure.

### Example

$\displaystyle \int { \frac { 1 }{ \left( x-3 \right) \sqrt { x+1 } } } dx$

Solution:

$\displaystyle Let\quad I=\int { \frac { 1 }{ \left( x-3 \right) \sqrt { x+1 } } } dx$

Here P and Q both are linear, so we put

$\displaystyle Q={ t }^{ 2 }\quad i.e.,\quad x+1={ t }^{ 2 }\quad so\quad that\quad dx=2t\quad dt\\ \therefore I=\int { \frac { 1 }{ \left( { t }^{ 2 }-1-3 \right) } \frac { 2t }{ \sqrt { { t }^{ 2 } } } } dt\\ =2\int { \frac { dt }{ { t }^{ 2 }-{ 2 }^{ 2 } } } \\ =2.\frac { 1 }{ 2\left( 2 \right) } \log { \left| \frac { t-2 }{ t+2 } \right| } +C\\ =\frac { 1 }{ 2 } \log { \left| \frac { \sqrt { x+1 } -2 }{ \sqrt { x+1 } +2 } \right| } +CÂ Â$

### Type II

Integrals of the formÂ $\displaystyle \int { \frac { \phi \left( x \right) }{ P\sqrt { Q } } } dx$ where P is a quadratic expression and Q is a linear expression

To evaluate this type of integrals we putÂ $\displaystyle Q={ t }^{ 2 }$ i.e. to evaluate integrals of the form $\displaystyle \int { \frac { 1 }{ \left( a{ x }^{ 2 }+bx+c \right) \sqrt { px+q } } } dx,\quad put\quad px+q={ t }^{ 2 }$

### Example

$\displaystyle \int { \frac { 1 }{ \left( { x }^{ 2 }-4 \right) \sqrt { x+1 } } } dx$

Solution:

$\displaystyle Let\quad I=\int { \frac { 1 }{ \left( { x }^{ 2 }-4 \right) \sqrt { x+1 } } } dx\\ Put\quad x+1={ t }^{ 2 }\quad so\quad that\quad dx=2t\quad dt$

$\displaystyle \therefore I=\int { \frac { 2t }{ \left[ { \left( { t }^{ 2 }-1 \right) }^{ 2 }-4 \right] \sqrt { { t }^{ 2 } } } dt } \\ =2\int { \frac { dt }{ \left( { t }^{ 2 }-1-2 \right) \left( { t }^{ 2 }-1+2 \right) } } \\ =2\int { \frac { dt }{ \left( { t }^{ 2 }-3 \right) \left( { t }^{ 2 }+1 \right) } } Â$

$\displaystyle Let\quad { t }^{ 2 }=y\quad then\\ \frac { 1 }{ \left( { t }^{ 2 }-3 \right) \left( { t }^{ 2 }+1 \right) } =\frac { 1 }{ \left( y-3 \right) \left( y+1 \right) } \\ \frac { 1 }{ \left( y-3 \right) \left( y+1 \right) } =\frac { 1 }{ \left( y-3 \right) } +\frac { B }{ \left( y+1 \right) } \qquad .......\left( i \right) \\ \Rightarrow 1=A\left( y+1 \right) +B\left( y-3 \right) \qquad .......\left( ii \right) Â$

Putting y=-1 , 3 respectively in (ii) , we getÂ $\displaystyle B=-\frac { 1 }{ 4 } \quad and\quad A=\frac { 1 }{ 4 }Â$

Substituting the values of A and B in (i) we obtain

$\displaystyle \frac { 1 }{ \left( y-3 \right) \left( y+1 \right) } =\frac { 1 }{ 4\left( y-3 \right) } -\frac { 1 }{ 4\left( y+1 \right) } \\ \Rightarrow \frac { 1 }{ \left( { t }^{ 2 }-3 \right) \left( { t }^{ 2 }+1 \right) } =\frac { 1 }{ 4\left( { t }^{ 2 }-3 \right) } -\frac { 1 }{ 4\left( { t }^{ 2 }+1 \right) } Â$

$\displaystyle So,\quad I=2\int { \left( \frac { 1 }{ 4\left( { t }^{ 2 }-3 \right) } -\frac { 1 }{ 4\left( { t }^{ 2 }+1 \right) } \right) } dt\\ =\frac { 1 }{ 2 } \int { \frac { 1 }{ { t }^{ 2 }-{ \left( \sqrt { 3 } \right) }^{ 2 } } dt } -\frac { 1 }{ 2 } \int { \frac { 1 }{ { t }^{ 2 }+{ 1 }^{ 2 } } } dt$

$\displaystyle =\frac { 1 }{ 2 } .\frac { 1 }{ 2\sqrt { 3 } } \log { \left| \frac { t-\sqrt { 3 } }{ t+\sqrt { 3 } } \right| } -\frac { 1 }{ 2 } \tan ^{ -1 }{ \left( t \right) } +C\\ =\frac { 1 }{ 4\sqrt { 3 } } \log { \left| \frac { \sqrt { x+1 } -\sqrt { 3 } }{ \sqrt { x+1 } +\sqrt { 3 } } \right| } -\frac { 1 }{ 2 } \tan ^{ -1 }{ \left( \frac { \sqrt { x+1 } }{ 1 } \right) } +C$

### Type III

Integrals of the formÂ $\displaystyle \int { \frac { \phi \left( x \right) }{ P\sqrt { Q } } } dx$ where P is a linear expression and Q is a quadratic expression

To evaluate this type of integrals we putÂ $\displaystyle p=\frac { 1 }{ t } Â$ i.e. to evaluate integrals of the formÂ $\displaystyle \int { \frac { 1 }{ \left( ax+b \right) \sqrt { p{ x }^{ 2 }+qx+r } } } dx\quad put\quad ax+b=\frac { 1 }{ t } Â$

### Example

$\displaystyle \int { \frac { 1 }{ \left( x+1 \right) \sqrt { { x }^{ 2 }-1 } } } dx$

Solution:

$\displaystyle Let\quad I=\int { \frac { 1 }{ \left( x+1 \right) \sqrt { { x }^{ 2 }-1 } } } dx\quad Put\quad x+1=\frac { 1 }{ t } \quad so\quad that\quad \\dx=-\frac { 1 }{ { t }^{ 2 } } dt$

$\displaystyle \therefore I=\int { \frac { 1 }{ \frac { 1 }{ t } \sqrt { { \left( \frac { 1 }{ t } -1 \right) }^{ 2 }-1 } } } .\left( -\frac { 1 }{ { t }^{ 2 } } \right) dt\\ =-\int { \frac { dt }{ \sqrt { 1-2t } } } \\ =-\int { { \left( 1-2t \right) }^{ -\frac { 1 }{ 2 } } } dt$

$\displaystyle =-\frac { { \left( 1-2t \right) }^{ \frac { 1 }{ 2 } } }{ \left( -2 \right) \left( \frac { 1 }{ 2 } \right) } +C\\ =\sqrt { 1-2t } +C\\ =\sqrt { 1-\frac { 2 }{ x+1 } } +C\\ =\sqrt { \frac { x-1 }{ x+1 } } +C$

### Type IV

Integrals of the formÂ $\displaystyle \int { \frac { \phi \left( x \right) }{ P\sqrt { Q } } } dx$ where P and Q both are pure quadratic expression inÂ  x i.e.Â $\displaystyle P=a{ x }^{ 2 }+b\quad and\quad Q=c{ x }^{ 2 }+d$

To evaluate this type of integrals we putÂ $\displaystyle x=\frac { 1 }{ t }Â$ and thenÂ $\displaystyle c+d{ t }^{ 2 }={ u }^{ 2 }$ i.e., to evaluate integrals of the form

$\displaystyle \int { \frac { 1 }{ \left( a{ x }^{ 2 }+b \right) \sqrt { c{ x }^{ 2 }+d } } } dx\quad we\quad put\quad x=\frac { 1 }{ t } \quad to\quad obtain\quad \int { \frac { -tdt }{ \left( a+b{ t }^{ 2 } \right) \sqrt { c+d{ t }^{ 2 } } } } \quad and\quad then\quad \\ c+d{ t }^{ 2 }={ u }^{ 2 }$

### Example

$\displaystyle \int { \frac { 1 }{ { x }^{ 2 }\sqrt { 1+{ x }^{ 2 } } } } dx$

Solution:

$\displaystyle Let\quad I=\int { \frac { 1 }{ { x }^{ 2 }\sqrt { 1+{ x }^{ 2 } } } } dx\quad Put\quad x=\frac { 1 }{ t } \quad so\quad that\quad -\frac { 1 }{ { x }^{ 2 } } dx=dt\quad or\quad dx=-{ x }^{ 2 }dt$

$\displaystyle \therefore I=\int { \frac { -dt }{ \sqrt { 1+\frac { 1 }{ { t }^{ 2 } } } } } \\ =-\int { \frac { t\quad dt }{ \sqrt { { t }^{ 2 }+1 } } } \\ =-\int { \frac { u\quad du }{ \sqrt { { u }^{ 2 } } } } \\ where\quad { t }^{ 2 }+1={ u }^{ 2 }$

$\displaystyle =\int { -1 } du\\ =-u+C\\ =-\sqrt { { t }^{ 2 }+1 } +C\\ =-\sqrt { \frac { 1 }{ { x }^{ 2 } } +1 } +C\\ =-\frac { \sqrt { 1+{ x }^{ 2 } } }{ x } +C$

April 18, 2019
Which class you are presently in?
Choose an option. You can change your option at any time.
You will be solving questions and growing your critical thinking skills.